Pengembangan Sistem Informasi dan Aplikasi Pengajuan Izin berbasis Android (Studi Kasus: Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Ponorogo) - Arief Dwi Kurniawan; Welly Purnomo; Kariyoto Kariyoto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) is a Ponorogo Regency Government Institution that is engaged in investment and licensing services with a one-stop system. However, based on the results of the researcher's interview with the Head of Service Division of DPMPTSP Ponorogo Regency, there are problems in licensing services. This is because there is already a-based licensing information system, web but in its application, the public as applicants for licensing documents still experience problems in applying for permits and uncertainty in the processing time of documents. To solve these problems, an effective and easier-to-use information system is needed in licensing services. The purpose of this research is to develop Sistem Informasi Perizinan Terpadu (SIPT) and android application that uses the SDLC method Waterfall. SIPT will be the backend of the based permit application which android will be the frontend of the application. The system design is carried out using an object-oriented paradigm, while the system implementation is carried out using Laravel framework for the backend and Android Studio for the frontend application which is integrated using web services. The testing phase is carried out using Validation Testing which obtains valid results for all application functionality, as well as by conducting User Acceptance Testing for stakeholders which produces an acceptance value of 80% and Compatibility Testing using Android Virtual Device (AVD) produces compatible results for all devices tested.